‘Mind the (Knowledge) Gap’: Towards a Criminal Duty to Report Child Sexual Abuse? - Renée Sharon Barbara Kool (Utrecht University School of Law, 2021)
Over the past few decades, child sexual abuse (‘CSA’) has become recognized as a serious and major problem in modern societies. Consequently, a common denominator in modern government policy is that CSA must be criminalized and pro-actively enforced. However, if national authorities are to be able to enforce, knowledge about the abuse is essential. Yet the disclosing of information to the authorities is hampered by the hidden nature of the offence. According to the Council of Europe Convention on the Protection of Children against Sexual Exploitation and Sexual Abuse (Lanzarote) and EU Directive 2011/93 on combating the sexual abuse and sexual exploitation of children, Member States should ‘encourage any person’ who knows about or suspects CSA to report this to the relevant authorities. To encourage such disclosure, several European governments have introduced mandatory reporting systems imposing a (non-criminal) duty on designated professionals to report information about or suspicions of CSA to the competent authorities. This article examines whether introducing a criminal duty to report CSA could be recommendable for the European Union or the Council of Europe in order to improve Member States’ knowledge of CSA and thus protect children more effectively against this type of violence. Using the outcomes of our recent study into the possibilities and impossibilities of extending the present Dutch criminal duty ('aangifteplicht') to report rape, we argue that a criminal duty to report CSA is not recommendable as a means to encourage CSA disclosure by third parties.